Heart-rate variability threshold as an alternative for spiro-ergometry testing: A validation study - Mankowski, R. T.; Michael, S.; Rozenberg, R.; Stokla, S.; Stam, H. J.; Praet, S. F. E. (The Journal of Strength and Conditioning Research, 2017)
Although spiro-ergometry is the established "gold standard" for determination of the second ventilatory threshold (VT2), it is a costly and rather time-consuming method. Previous studies suggest that assessing the second anaerobic threshold (AT2) on the basis of heart rate variability (HRV) during exercise may be a more cost-effective and noninvasive manner. However, appropriate validation studies, are still lacking. Eleven healthy, moderately trained subjects underwent 3 incremental exercise tests. Ventilation, oxygen uptake (VO2), CO2 production (VCO2), and HRV were measured continuously. Exercise testing was performed in 3 oxygen (FiO2) conditions of inspired air (14, 21, and 35% of oxygen). Participants and assessors were blinded to the FiO2 conditions. Two research teams assessed VT2s and HRVT2s independently from each other. Mean workloads corresponding to VT2 and HRVT2 in hypoxia were, respectively, 19 ± 17% (p = 0.01) and 15 ± 15% (p = 0.1) lower in comparison with hyperoxic conditions. Bland-Altman analysis showed low estimation bias (2.2%) and acceptably precise 95% limits of agreement for workload -15.7% to 20.1% for all FiO2 conditions. Bias was the lowest under normoxic conditions (1.1%) in comparison with hypoxia (3.7%) and hyperoxia (4.7%). Heart rate variability-based AT2 assessment had a most acceptable agreement with VT2 under normoxic conditions. This simple HRVT2 assessment may have potential applications for exercise monitoring in commercial fitness settings.